PENGARUH SELEKSI DAN PENEMPATAN TERHADAP KINERJA KARYAWAN DI AMARIS HOTEL LEGIAN BALI - I Gede Agus Widarsana; I Made Hedy Wartana (Journal Research of Management, 2020)
Quality The performance of employees at Amaris Hotel Legian Bali is inseparable from the selection and placement process carried out on site. both in conducting the selection process that is passed through the academic selection through a CV that has been sent, then by field interviews with the department head according to the applicant, then selection of health tests with a health certificate and some health test results sent to the place, and then the final interview test with the hotel leadership is the Hotel Manager Amaris Hotel Legian. Then placed or through the placement process by placing prospective employees in accordance with what prospective employees apply. This study functions and aims to analyze the effect of selection and placement on employee performance at Amaris Hotel Legian Bali. where the number of samples in this study were 75 respondents, namely all employees working on the research object. Data collection techniques in this study using a questionnaire and documentation. The research method used in this study is a quantitative method. In multiple linear regression analysis obtained the following regression equation Y = 8.597 + 0.495X1 + 0.278X2. in addition to this it is also proven that the Effect of Selection on Employee Performance at Amaris Hotel Legian Bali is a positive and significant effect as evidenced by the significance value of less than 0.05 which is equal to 0,000. while the Effect of Placement on Employee Performance at Amaris Hotel Legian Bali is a positive and significant effect as evidenced by the significance value smaller than 0.05 which is equal to 0.002. for the effect of Selection and Placement on Employee Performance at Amaris Hotel Legian Bali is 33.8%